Venture capital financing, moral hazard, and learning - Bergemann, Dirk; Hege, Ulrich (Journal of Banking & Finance, 1998)
We consider the provision of venture capital in a dynamic agency model. The value of the venture project is initially uncertain and more information arrives by developing the project. The allocation of the funds and the learning process are subject to moral hazard. The optimal contract is a time-varying share contract which provides intertemporal risk-sharing between venture capitalist and entrepreneur. The share of the entrepreneur reflects the value of a real option. The option itself is based on the control of the funds. The dynamic agency costs may be high and lead to an inefficient early stopping of the project. A positive liquidation value explains the adoption of strip financing or convertible securities. Finally, relationship financing, including monitoring and the occasional replacement of the management improves the efficiency of the financial contracting.